2019
DOI: 10.1002/jia2.25296
|View full text |Cite
|
Sign up to set email alerts
|

The role of costing in the introduction and scale‐up of HIV pre‐exposure prophylaxis: evidence from integrating PrEP into routine maternal and child health and family planning clinics in western Kenya

Abstract: Introduction Understanding the cost of strategies to reach and deliver pre‐exposure prophylaxis (PrEP) to priority populations is essential to assess the cost‐effectiveness and budget impact of HIV prevention programmes. Providing PrEP through maternal and child health and family planning clinics offers a promising strategy to reach women in high HIV burden settings. We estimated incremental costs and explored the cost drivers of integrating PrEP delivery into routine maternal and child health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 32 publications
(35 reference statements)
7
36
1
1
Order By: Relevance
“…Integration of PrEP into platforms that provide health care, such as family planning services and STI testing, can share administrative costs thus decreasing the cost of PrEP delivery. Routine programme evaluation, including costing, can be used to estimate the cost of streamlined PrEP delivery within and outside facilities .…”
Section: Resultsmentioning
confidence: 99%
“…Integration of PrEP into platforms that provide health care, such as family planning services and STI testing, can share administrative costs thus decreasing the cost of PrEP delivery. Routine programme evaluation, including costing, can be used to estimate the cost of streamlined PrEP delivery within and outside facilities .…”
Section: Resultsmentioning
confidence: 99%
“…We obtained facility staff and ministry of health (MoH) salaries from communication with site staff and publicly-available information on job groups and basic allowances (housing and commuter) per job cadre [ 11 ]. Public sector cost per bottle of tenofovir disoproxil fumarate/emtricitabine (TDF/FTC, $6.25 in 2017 US dollars) was obtained from recently published data from Kenya [ 8 ]. We conducted time-and-motion observations to record the time spent by providers during each direct PrEP delivery activity.…”
Section: Methodsmentioning
confidence: 99%
“…However, these models had fixed assumptions about the cost of PrEP per person-year and did not use data from real-world implementation settings. To date, only one study has reported the cost of delivering PrEP to AGYW in sub-Saharan Africa using practical data from implementation [ 8 ], and more evidence is needed on the cost of delivering PrEP to this population.…”
Section: Introductionmentioning
confidence: 99%
“…They estimate that up to 70% of all new HIV infections could have been averted if sex work interventions had achieved complete coverage in 2010; while they recognize the limitations of this as a model, the paper raises an important point by showing that appropriate scaling of interventions is essential if they are to have impact at a population level. One obstacle to such scale‐up for programmes is cost, and this is addressed in the paper by Roberts and colleagues . Using data from a PrEP implementation project in Kenya, they identified costs of the programme and explored different scenarios to show that incremental costs were sensitive to the delivery approach and the extent to which monitoring, for example routine creatinine testing, were included.…”
Section: Banbury Meeting and Supplementmentioning
confidence: 99%